Determination of nitenpyram and 6‐chloronicotinic acid in environmental samples by ion chromatography coupled with online photochemically induced fluorescence detector. Issue 22 (9th October 2018) - Muhammad, Nadeem; Zhang, Yun; Li, Weixia; Zhao, Yong‐Gang; Ali, Amjad; Subhani, Qamar; Mahmud, Tariq; Liu, Junwei; Cui, Hairong; Zhu, Yan
Abstract: A simple, cost‐effective, sensitive, and quick method for the determination of nitenpyram and its metabolite 6‐chloronicotinic acid in environmental samples was developed by coupling an ion chromatograph with a fluorescence detector and a post‐column photochemical reactor. This developed analytical method involved a rapid sample extraction by modified and miniaturized quick, easy, cheap, effective, rugged, and safe method followed by isocratic ion chromatographic separation of nitenpyram and 6‐chloronicotinic acid into an IonPac ™ AS11‐HC column protected by IonPac ™ AG11A guard column by running 30 mM NaOH + 10% acetonitrile mobile phase. A homemade post‐column photochemical reactor was also integrated with the ion chromatographic system for online transformation of both analytes into their respective highly fluorescent photoproduct in basic media without using an extra pump. The developed method was validated by following SANTE/11945/2015 guidelines on analytical quality control and validation procedures. The method showed a good linear response (r > 0.999), improved limit of detection (0.101–0.132 μg/L), minimum or no matrix effect, excellent recoveries (90.2–100.10%) and relative standard deviations were found to be ≤6.50%.